CACHERP: A novel dynamic cache size tuning model working with relative object popularity for fast web information retrieval - Wu, R.; Wong, A.; Dillon, Tharam S. (Springer-Verlag, 2006)
The CACHERPframework leverages the relative object popularity as the sole parameter for dynamic cache size tuning. In the process it consistently maintains the prescribed cache hit ratio on the fly by deriving the popularity ratio from the current statistics. As a result the accuracy of the statistical CACHERPoperation is independent of changes in the Internet traffic pattern that may switch suddenly. The contribution by the novel CACHERPframework is that by adaptively maintaining the given hit ratio it effectively reduces the end-to-end information retrieval roundtrip time (RTT) and frees more bandwidth for sharing. This bandwidth would otherwise be consumed in transferring large amounts of data from remote data sources to the proxy server before it is given to the client or requestor.